Brown adipose tissue-derived exosomes delay fertility decline in aging mice - Zhang, Hanke; Fang, Yuqing; Gao, Ying; Zeng, Xinliu; Lu, Zhenzhen; Liu, Lin; Chen, Chunyan; Huang, Jiayu; Li, Yanhui (Frontiers in Endocrinology, 2023)
Introduction: Ovarian aging has steadily grown to be a significant health issue for women as a result of the increase in average life expectancy and the postponement of reproductive age. One of the important pathological foundations of ovarian aging is formed by mitochondrial dysfunction, which causes decreases in follicle quantity and oocyte quality. In recent years, brown adipose tissue (BAT) transplantation has been proven as an effective treatment for aging-related diseases, such as ovarian aging. However, BAT transplantation is an invasive operation with long-term risks. Therefore, we need to find an alternative strategy. Methods: We injected BAT-derived exosomes into eight-month-old C57BL/6 female mice. The fertility was detected by the estrous cycle and mating test. The changes of ovary and oocyte were measured by ovarian volume, organ coefficient, follicle counting, and oocyte maturation rate. ROS level, mitochondrial membrane potential and ATP level were measured to analyze the mitochondrial function of oocytes. The changes in metabolism were explored by cold stimulation test, body weight and blood sugar. The possible molecular mechanism was further investigated by RNA sequencing. Results: In terms of fertility, the estrous cycle of aging mice after BAT-derived exosome intervention was more regular, and the number of progenies and litters was increased. At the tissue level, the ovaries in the BAT-exosome group were larger, and the number of primordial follicles, secondary follicles, antral follicles and total follicles increased. At the cellular level, BAT-derived exosomes improved the maturation of oocytes in vivo and in vitro, increased the mitochondrial membrane potential and ATP levels of oocytes, and decreased ROS levels. Besides, BAT-derived exosomes ameliorated the metabolism and viability of aging mice. Furthermore, mRNA sequencing showed that BAT exosomes altered the expression levels of genes related to metabolism and the quality of oocytes. Conclusion: BAT-derived exosomes enhanced mitochondrial function, promoted follicle survival, improved fertility, and extended ovarian lifespan in aging mice.